The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1179/jmt.2008.16.3.155
|View full text |Cite
|
Sign up to set email alerts
|

Predictor Variables for a Positive Long-Term Functional Outcome in Patients with Acute and Chronic Neck and Back Pain Treated with a McKenzie Approach: A Secondary Analysis

Abstract: A cognitive behavioral approach was previously compared to a biomechanical approach (the McKenzie method) for the treatment of patients with back and neck pain in a randomized trial. Few differences between the treatment interventions were found. The aim of this secondary analysis was to determine if any clinical characteristics distinguished those patients who responded best to the McKenzie approach. Treatment success was defined as 50% reduction in original functional disability scores (Roland-Morris Disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
(58 reference statements)
2
19
0
4
Order By: Relevance
“…Centralisation as seen in patients with low back pain (LBP) has been found to be an excellent predictor of a favourable outcome. [12][13][14][15][16][17][18] Although Edmond et al found individuals with neck pain who presented with CEN or a directional preference demonstrated improvements in functional outcomes, 14 the research is limited. Therefore, the purpose of this study is to determine the relationship between CEN and outcome in people with neck pain and peripheral symptoms who are treated in physical therapy according to the MDT approach.…”
Section: Introductionmentioning
confidence: 99%
“…Centralisation as seen in patients with low back pain (LBP) has been found to be an excellent predictor of a favourable outcome. [12][13][14][15][16][17][18] Although Edmond et al found individuals with neck pain who presented with CEN or a directional preference demonstrated improvements in functional outcomes, 14 the research is limited. Therefore, the purpose of this study is to determine the relationship between CEN and outcome in people with neck pain and peripheral symptoms who are treated in physical therapy according to the MDT approach.…”
Section: Introductionmentioning
confidence: 99%
“…9 Although certain occupations such as office and computer workers, manual labourers, and health care workers, have been found in some studies to have a higher incidence of neck pain, the major workplace factors associated with the condition are low job satisfaction and perceived poor workplace environment. 10 Unique risk factors for neck pain include trauma (e.g., traumatic brain and whiplash injuries) and certain sports injuries (eg, wrestling, ice hockey, football).In our study 14.1% of the patients gave a history of neck injury. In a study conducted by, Donald R Murphy et al it is found that individuals who have experienced trauma in the neck are at increased risk of developing neck pain and 20% of patients in his study had neck injury.…”
Section: 2mentioning
confidence: 96%
“…In addition, a recent secondary analysis of predictors of longterm functional outcome in patients with acute and chronic spinal pain treated by the MDT approach failed to demonstrate any significant prognostic value of pain response classification. 22 Accordingly, the predictive value of pain classification in secondary care may be questioned.…”
Section: Discussion Imentioning
confidence: 99%